The Practice of Medical Care Convicted to Imprisonment in Russia and Abroad - Lavrukhina A. (Bulletin of Science and Practice, 2019)
Investigates the international practice of providing medical care to convicts to imprisonment. Based on the results of the analysis of domestic legislation and the current foreign practice, the author makes the following conclusions. The concept of development of the penal system of the Russian Federation until 2020 in the aspect of providing medical care to convicts cannot be implemented in full because of problems in the field of material and technical, personnel, medical, resource support of correctional institutions. The study of the experience of foreign countries shows that the penal system uses both the model of sending patients to external medical institutions and the model by which medical personnel are sent from the national service to the prison. In a number of countries, Denmark, Hungary, Ireland, Sweden have adopted mixed funding through the national health service and prison administration, and in England and Wales, Iceland, Cyprus, Norway funding is provided through the national health system. An analysis of practice shows that in Belgium, Ireland, Lithuania, it is generally not accepted to transfer prisoners from places of detention to hospitals for treatment, in England and Wales, Bulgaria, Denmark, the Netherlands, Norway and France, the hospitals themselves are responsible for the safety of the transfer of prisoners. In the rest of the countries, the security of the transfer is ensured by prison guards or the police. The author concludes that the introduction of national standards for the management of patients, including a wide range of diseases, into the penitentiary system of Russia presents significant difficulties. One of the main obstacles is the structure of the medical service of the penitentiary system, the analogue of which does not exist in public health. With such a volume of health care, the existing structure of material and technical equipment, the staff of the medical unit, as well as insufficient funding do not allow to fully adhere to medical and economic standards.